Characterizing Researchers by Strategies Used for Retaining Minority Participants: Results of a National Survey - Butler, James (2013)
Limited attention has been given to the optimal strategies for retaining racial and ethnic minorities within studies and during the follow-up period. High attrition limits the interpretation of results and reduces the ability to translate findings into successful interventions. This study examined the retention strategies used by researchers when retaining minorities in research studies. From May to August 2010, we conducted an online survey with researchers (principal investigators, research staff, and IRB members) and examined their use of seven commonly used retention strategies. The number and type of retention strategies used, how these strategies differ by researcher type, and other characteristics (e.g., funding) were explored. We identified three clusters of researchers: comprehensive retention strategy researchers - utilized the greatest number of retention strategies; moderate retention strategy researchers - utilized an average number of retention strategies; and limited retention strategy researchers - utilized the least number of retention strategies. The comprehensive and moderate retention strategy researchers were more likely than the limited retention strategy researchers to conduct health outcomes research, work with a community advisory board, hire minority staff, use steps at a higher rate to overcome retention barriers, develop new partnerships with the minority community, modify study materials for the minority population, and allow staff to work flexible schedules. This study is a novel effort to characterize researchers, without implying a value judgment, according to their use of specific retention strategies. It provides critical information for conducting future research to determine the effectiveness of using a combination of retention strategies.